The Effect of Business Orientation on Small Business Performance in Kendari City - Riski Amalia Madi; Buyung Sarita; Agustinus Tangalayuk; Ece Yulianti (CV. Literasi Indonesia, 2021)
Small businesses engaged in the food industry sector in the city of Kendari is a business activity that is broadly classified as small and is built by individuals or middle-to-lower groups. The purpose of business development is to earn profits with different levels of performance. One factor that can affect performance is the dimension of entrepreneurial orientation which consists of innovation, proactivity, risk-taking, competitive aggressiveness, and autonomy. The purpose of this study is to examine and provide empirical evidence about the effect of entrepreneurial orientation on the performance of small businesses. The sampling technique in this study uses the probability sampling technique. The analysis used is quantitative analysis using multiple linear regression analysis and quantitative data processing using SPSS 24.0. The results of the analysis using multiple linear regressions found that innovation, proactivity, risk-taking, and competitive aggressiveness have a positive and significant effect on the performance of Small and Medium Enterprises. While autonomy has a positive and not significant effect on the performance of small businesses.